2020
DOI: 10.1186/s12985-020-01393-z
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden of chronic hepatitis B and complications in China from 2006 to 2050: an individual-based modeling study

Abstract: Background: Chronic hepatitis B has become a major public health problem in China. An accurate depiction of the disease burden has not yet been thoroughly conducted. We aimed to project the disease burden of chronic hepatitis B virus (HBV) infection and related complications by modeling various scenarios. Method: An individual-based Markov model was used to predict disease burden from 2006 through 2050. We simulated 5 scenarios with different annual incidences, diagnoses and nucleotide analog (NA) treatment ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…It was reported that the three major causes of disability in China were musculoskeletal diseases, mental illnesses, and sensory organ diseases in 2017 (24). The incidence of infectious diseases and digestive system diseases is expected to decline slowly, while the incidence of chronic diseases such as diabetes will continue to explode (26)(27)(28). There are significant differences in drug structure between China and the globe.…”
Section: Trials Guided By Clinical Value In Chinamentioning
confidence: 99%
“…It was reported that the three major causes of disability in China were musculoskeletal diseases, mental illnesses, and sensory organ diseases in 2017 (24). The incidence of infectious diseases and digestive system diseases is expected to decline slowly, while the incidence of chronic diseases such as diabetes will continue to explode (26)(27)(28). There are significant differences in drug structure between China and the globe.…”
Section: Trials Guided By Clinical Value In Chinamentioning
confidence: 99%
“…Improving the identification of chronically infected individuals is a key component to addressing the chronic HBV burden in China 6 . It is described as a ‘silent epidemic’ 1 reflecting the asymptomatic disease course that contributes to late diagnosis and poor prognosis – in China the diagnosis rate is estimated at less than 20%, well below the World Health Organization (WHO) target of 90% by 2030 7 , 8 . However, apart from risk factors contributing to mother to child transmission, comparatively little is known about risk factors for HBV chronicity in adults, and the most recent nationwide Hepatitis B serosurvey in China in 2014 only included participants aged 1–29 years 9 .…”
Section: Introductionmentioning
confidence: 99%
“…China has the greatest disease burden of liver cirrhosis in the world ( 9 ). In China, the number of patients with liver cirrhosis accounts for 20% of the total number of patients with chronic liver disease, most of whom are aged between 20 and 50 years ( 10 ).…”
Section: Introductionmentioning
confidence: 99%